Izkušnje iz poletnih priprav kegljačev - Bajec, Bojan (Šport (Ljubljana), 2016)
Preparation of summer camp is demanding project and requires a lot of responsibility of the organization, managers and coaches. Over the years, since we conducted summer camp, we have found that for the health of our nine pins bowlers is the most important transmission of information on their biopsychosocial status and how to plan, execute and control themselves at workouts and competitions. At the same time we should emphasize the educational aspect, which have significant impact on their further sports career.
Keywords: education; exercise; kegljanje; nine pin bowling; odmor; priprave; rest; sport; šport; training; vadba; vzgoja in izobraževanje